Facultative Sex Allocation and Sex‐Specific Offspring Survival in Barrow's Goldeneyes. (13th December 2012) - Jaatinen, Kim; Öst, Markus; Gienapp, Phillip; Merilä, Juha; Wright, J.
Abstract Sex allocation theory predicts that females should bias their reproductive investment towards the sex generating the greatest fitness returns. The fitness of male offspring is often more dependent upon maternal investment, and therefore, high‐quality mothers should invest in sons. However, the local resource competition hypothesis postulates that when offspring quality is determined by maternal quality or when nest site and maternal quality are related, high‐quality females should invest in the philopatric sex. Waterfowl – showing male‐biased size dimorphism but female‐biased philopatry – are ideal for differentiating between these alternatives. We utilized molecular sexing methods and high‐resolution maternity tests to study the occurrence and fitness consequences of facultative sex allocation in Barrow's goldeneyes (Bucephala islandica). We determined how female structural size, body condition, nest‐site safety and timing of reproduction affected sex allocation and offspring survival. We found that the overall sex ratio was unbiased, but in line with the local resource competition hypothesis, larger females produced female‐biased broods and their broods survived better than those of smaller females. This bias occurred despite male offspring being larger and tending to have lower post‐hatching survival. The species shows strong female breeding territoriality, so the benefit of inheriting maternal quality by philopatric daughters may exceed the potential mating benefit for sons of high‐quality females.